THE IMPROVEMENT PRODUCTION CHICKEN FEED BY FERMENTATION AND EGG INCUBATOR IN MALANG VILLAGE - Dahliatul Qosimah (Journal of Innovation and Applied Technology, 2017)
The purpose of this public service activities is to help improve productivity and accelerate egg hatchability of eggs using appropriate technology incubator eggs that are expected to improve the economy of the people in the district of Malang apart from that application's use of fermented feed can improve the digestibility so that growth can be maximized. IbM's results show that community service is very enthusiastic partners with activities provided by the team, the use of egg incubators can improve hatchability of eggs in bulk to minimize the time the hatch and feed fermentation using Aspergillus orizae can increase the protein content of crude protein feed from 12.09 to 19 , 77 and lower crude fiber of 7.99 becomes 3.83, which improves the performance egg quality (larger size and eggshell color dark brown). A direct partner to practice the use of the incubator incubator capable hatch into chicks and want to practice the use of chicken feed fermentation.